A theoretical study of the electrochemical reduction of CO2 on cerium dioxide supported palladium single atoms and nanoparticles. Issue 46 (23rd November 2021) - Guo, Yannv; Zhu, Haiyan; Zhao, He; Zhao, Qinfu; Zhou, Caihua; Suo, Bingbing; Zou, Wenli; Jiang, Zhenyi; Li, Yawei
Abstract : The higher catalytic activity of cerium dioxide supported Pd8 nanoparticles over the supported single atoms was demonstrated by comparing the overpotential of the best reaction path. Abstract : Pd/CeO2 catalysts show superior catalytic performance owing to their optimal cycling activity and stability. In this study, single-atom Pd and eight-atom Pd nanoparticle clusters were supported on the surface of CeO2 (110) to investigate the effect of loaded-metal size on the catalytic performance of the Pd–CeO2 system for CO2 reduction. We investigated the CO2 reduction reaction (CRR) that produces C1 products (CO, HCOOH, CH3 OH, and CH4 ) on Pd8 /CeO2 and Pd/CeO2 by density functional theory. The structures, CO2 adsorption configurations, and CO2 reduction mechanisms of these two electrocatalysts were systematically studied. Subsequently, different reduction pathways on Pd8 /CeO2 and Pd/CeO2 were investigated to identify the optimal reaction pathway for further assessment. The results showed that both of these catalysts are more selective towards the production of CH3 OH than CH4 . Moreover, compared to Pd/CeO2 and Pd4 /CeO2 (from a previously reported study) the production of CH3 OH via the CRR on Pd8 /CeO2 exhibited the lowest limiting potential. These results demonstrate the superiority of Pd8 /CeO2 as an electrocatalyst for the electrochemical reduction of CO2 to CH3 OH.